A fault-tolerant attitude tracking control of spacecraft using an anti-unwinding robust nonlinear disturbance observer. (December 2019) - Amrr, Syed Muhammad; Nabi, M; Tiwari, Pyare Mohan
This paper investigates the application of an integral sliding mode control with a robust nonlinear disturbance observer to obtain an anti-unwinding spacecraft attitude tracking response with robustness against external disturbances, inertia matrix uncertainties, and actuator faults. In the controller design, external disturbances, uncertainties, and actuator faults are lumped together and estimated by the robust nonlinear disturbance observer. The proposed robust nonlinear disturbance observer guarantees the convergence of estimated lumped disturbance error to origin in finite time. The estimated disturbance is then used in the controller as a feed-forward compensator. Further, an adaptive law is also incorporated in the proposed controller to ensure additional robustness. The stability of the overall system and anti-unwinding characteristic are proved using the Lyapunov stability theory. Finally, numerical simulation analysis is performed in the presence of all the sources of lumped disturbances. It is observed that the proposed control strategy is ensuring higher accuracy, good steady-state precision, and eliminates the unwinding phenomenon.